Low-cost water treatment system using submerged membrane filtration in developing countries. Issue 39 (20th August 2016) - Miyoshi, Taro; Setiadi, Tjandra; Effendi, Agus Jatnika; Maeda, Hiroyuki; Tsukaraha, Takashi; Yi, Hosang; Jun, Hyoyong; Saito, Masao; Matsuyama, Hideto
Abstract: In this study, we investigated the possibility of installing membrane-based water treatment technology in Indonesia. Due to high turbidity in river water, tremendous amount of chemicals (mainly coagulants) are often used in the water treatment process in Indonesia. Consumption of such chemicals can be alleviated using membrane filtration since complete rejection of particulate matter can be achieved by membranes without the necessity of coagulation. A pilot-scale membrane filtration unit was continuously operated for more than three months at an existing drinking water treatment plant in Bandung, Indonesia. The results indicated that the operation under a membrane flux of 45 L/m 2 /h and chemical maintenance cleaning frequency of once per two days was very stable, and almost no detectable membrane fouling was seen at this operating condition. At this condition, the operating expenditure of the membrane-based water treatment system was estimated to be nearly equal to that of a conventional water treatment system based on coagulation, sedimentation, and sand-filtration. A stable membrane filtration can also be achieved at a membrane flux of 50 L/m 2 /h and chemical maintenance cleaning frequency of once per week. The operating expenditure of this condition was estimated to be lower than that of the conventional treatment. However, the removal of iron and manganese by the membrane-based water treatment system was relatively poor; suggesting that some pretreatment for removing dissolved compounds is necessary. Results suggest that membrane-based water treatment systems are one of the economically attractive choices in Indonesia as long as cost-effective pretreatment is developed.